Teknologi Informasi sebagai Faktor Penggerak Ekonomi Mikro di Indonesia - Marpaung, Rita Boima Purnamasari; Ruslan, Dede (BUDGETING : Journal of Business, Management and Accounting, 2024)
This study investigates how information technology impacts the microeconomy in Indonesia. The purpose of this study is to provide an understanding of how the adoption of information technology affects the dynamics of the micro-economy at the local level by focusing on elements such as logistics efficiency, global market access, product and service innovation, micro-enterprise empowerment, and productivity improvement. This study concludes through theoretical studies and analysis of the results that information technology has many benefits, although there are problems that must be addressed, such as the digital divide and data security risks. A series of recommendations are made to maximize the benefits of information technology and encourage equitable microeconomic growth. Keyword: Information Technology, Microeconomics, Technology Adoption, Productivity